Prospects for the diagnosis and treatment of sarcopenia in the Philippines - Sun, Ji; Zhang, Weixin; Han, Peipei (Frontiers in Medicine, 2025)
Over the past decade, the elderly Filipino population has significantly increased, rising from 4.6 million seniors, which was approximately 6% of the total population in 2000, to 6.5 million, or around 6.9% of the population in 2010. Projections suggest that by 2030, the percentage of the population aged 60 and above will increase to between 10 and 19%, indicating a significant demographic shift toward an aging population. This shift from a predominantly young population to a rapidly growing elderly demographic underscores the urgent need for effective health promotion and management programs targeting older adults. Sarcopenia, a muscle-wasting disorder, represents a significant global health challenge, particularly affecting the elderly. In the Philippines, the impact of sarcopenia is expected to become more pronounced, potentially straining both individuals and the national healthcare system over the next 15 years, despite the country’s relatively younger overall population. Despite the expanding research on sarcopenia in the Philippines, there remains an urgent need to raise awareness and implement proactive measures to address this escalating health issue.